Debating Techniques in Language Learning to Trigger Students’ Communication in English and Critical Thinking - Yasyir Fahmi Mubaraq (STKIP PGRI Banjarmasin, 2016)
Being communicative has always been the crucial matter in any languages. People cannot be saidbeing able to use a language unless they can produce it. Some approaches of learning have also been raised all the time but the purpose of language for communication is hardly achieved by the foreign language learners. One of the problems is that students are too afraid in giving their opinions. Debating is one way to force our students to interact by using English and think critically. In a debate, students are divided into PRO and CON sides to criticize the issue given. By having a debate students can convey their ideas in certain issues along side with building their critical thinking. The idea of having a debate in the classroom is surely one of techniques in the teaching of English. This study tries to elaborate how some debate activities might be brought into classroom by always considering the varieties of Englishes that Indonesia belongs to. According to Kachru (1988:5), Indonesia is grouped into the expanding circle of World Englishes. Thus, the modified version of British, Australian, and Asian Parliamentary systems of debate are introduced for the sake of enhancing students’ speaking skills by always tolerating and exploiting the uniqueness of Indonesian Englishes